Collaborative printing and in-situ frontal curing of highly-viscous thermosetting composites. (3rd March 2023) - Gao, Chongjie; Liu, Ruochen; Li, Wei; Qiu, Jingjing; Wang, Shiren
Abstract: Rapid manufacturing of thermosets via frontal polymerization is very attractive for thermosetting composites due to the expected decarbonization and manufacturing flexibility with limited energy consumption; however, it is challenging for 3D printing and frontal curing of highly-viscous thermoset composites (e.g., >100, 000 mPa.s at room temperature) because of the rheology requirement of the 3D printing process and limited pot life of frontal curable resin inks under elevated temperature, which is usually used to reduce the viscosity of inks. We report an in-situ combining materials-based 3D printing process for printing and in-situ frontal curing of highly viscous thermosets. Specifically, an ultrasonic atomizer sprays the curing agent solution during the printing process to achieve an in-situ mixing with the resin oligomers at a microscale level. Multiphysics simulation indicated the curing degree distribution through the thickness direction and a printing window is provided depending on the extrusion deposition rate, the deposition layer thickness, and the ultrasonic sprayer amplitude. Further experiments were carried out, and it was found that the frontal velocity increased, and the frontal temperature remained almost unchanged with the rise of the ultrasonic amplitude. The curing degree and curing uniformity were improved with the increase of the ultrasonic amplitude but decreased with the increase of the printing layer thickness. Samples with different ultrasonic amplitudes and extrusion layer thicknesses were printed, and their mechanical properties were tested. The tensile strength and Young's modulus of novolac epoxy resin reached 47.56 MPa and 2.19 GPa, respectively. The feasibility of this method for composite printing was demonstrated. At a 5 wt% loading of short fibers, the tensile strength and Young's modulus of as-printed composites reached 66.71 MPa and 3.65 GPa. This method provides a fast and energy-efficient way to manufacture highly viscous thermosets and their composites.